Prevention of Increasing Total Cholesterol Level Using Cowpea Yoghurt - Maulana Rahmat Hidayatullah (Universitas Muhammadiyah Semarang, 2020)
Atherosclerosis is lipoprotein metabolism disorder which is marked by an increase of total cholesterol level in blood serum. Cowpea contains a lot of isoflavones that can inhibit the activity of the enzyme HMG-CoA reductase in the cholesterologenesis process. The aim of this study is to find out cowpea yogurt which can prevent the increasing total cholesterol level. This study used an experimental study with a post-test only control group design in 30 male rats. It was divided into 5 groups: Results showed that the total cholesterol level among the fifth group was a significant difference (Kruskal-Wallis, p = 0,000). The conclusion of this study is cowpea yogurt can prevent the increasing total cholesterol levels of Wistar rats induced by a high-fat diet.